Exploring Teachers' Perceptions of Curriculum Change and their Use of Textbooks during its Implementation. A Review of Current Research - Janko, Tomáš; Pešková, Karolína (Journal of Geography Education, 2017)
Curriculum change and its implementation into school instruction represent a complex process which has to be founded in a well-designed plan and supported by material and non-material factors in order to succeed. Key factors for successfully implementing a curriculum change include teachers and their attitudes, which may vary according to the sociocultural context. Textbooks are also an important factor among the frameworks and mechanisms that seek to guide curriculum change. In comparison to other factors, textbooks are more evident. The purpose of this study is to review the state of the art related to research on teacher perceptions of curriculum changes. The review is aimed primarily at the research findings and secondarily at the methodological aspects of studies examining this issue. Special focus is placed on the role of school textbooks as curriculum materials supporting the curriculum change implementation. In the review, 37 resources published between 2000 and 2015 were analysed. Twelve of the sources were related to the topic of teachers' use of textbooks during curriculum change implementation. The results of the review suggest that teacher perceptions of curriculum changes are not uniform, but vary between positions of acceptance and resistance. Teachers’ demographical characteristics (e.g. gender, years of teaching practice) and the perceived constraints of the implementation were identified as the factors most influencing stances towards the curriculum changes. It was also found that textbooks are still perceived as a key curricular (and instructional) tool by teachers. Teachers’ lack of pedagogical content knowledge was the most restraining factor in their use of textbooks during the implementation of the renewed curricula. The review concludes with suggestions for further research on teachers' perceptions towards curriculum changes and their use of textbooks during this process.
Keywords: curriculum reform, teacher perceptions, textbooks, review